2005
DOI: 10.1103/physreve.72.046139
|View full text |Cite
|
Sign up to set email alerts
|

Self-organized Boolean game on networks

Abstract: A model of a Boolean game with only one free parameter p that denotes the strength of local interaction is proposed wherein each agent acts according to the information obtained from his neighbors in the network, and those in the minority are rewarded. The simulation results indicate that the dynamic of the system is sensitive to network topology, whereby the network of larger degree variance, i.e., the system of greater information heterogeneity, leads to less system profit. The system can self-organize to a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
96
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(100 citation statements)
references
References 23 publications
4
96
0
Order By: Relevance
“…Numerical simulations show that the minority game displays a remarkably rich emergent collective behavior, which has been qualitatively understood to some extent by approximate schemes. Many extensions on the MG model have been developed, including strategy structure [4][5][6], strategy-selection [7,8], and payoff [9,10] function and strategy-evolution [11,12], agent-network-related [13][14][15][16] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations show that the minority game displays a remarkably rich emergent collective behavior, which has been qualitatively understood to some extent by approximate schemes. Many extensions on the MG model have been developed, including strategy structure [4][5][6], strategy-selection [7,8], and payoff [9,10] function and strategy-evolution [11,12], agent-network-related [13][14][15][16] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the dynamics of WL algorithm and search for optimal schedule for updating γ in order to achieve fast convergence to the true density of states with small statistical errors are under intensive studies. [31][32][33][34][35] Alternative methods for calculating the density of states are the broad histogram 15 and the transition matrix Monte Carlo (TMMC) methods. 17 It can be shown that the broad histogram method may be considered as a particular case of infinite temperature TMMC method 17 (see further in the text).…”
Section: Introductionmentioning
confidence: 99%
“…The special case with m = 0.01 and β = 0 has been previously studied to show the effect of degree heterogeneity on the dynamical behaviors [39].…”
Section: Modelmentioning
confidence: 99%